LONG-TERM RESULTS OF THREE-MODULE TREATMENT OF MUSCLE-INVASIVE BLADDER CANCER - Tillashaykhov M.N; Boyko.E.B; TuychiyevA.P; Alimov J.M (Scholar Express Journals, 2023)
to study the long-term results of three-modal therapy (TMT) of muscle-invasive bladder cancer (MIRMP) in a comparative aspect.
Keywords: three; modal therapy